Correlation between bacterial communities and organic acids in the fermentation stage of traditional Chinese sour porridge. Issue 1 (1st January 2020) - Guo, Haoxiang; Sun, Ziyu; Hao, Yuan; Zhang, Luyao; Ren, Yuting; Zhang, Yu; Chen, Zhongjun; Mandlaa
ABSTRACT: Fermented porridge is usually made though the process of natural fermentation of grains with higher starch. Organic acids are the main flavor compounds in fermented porridge. However, the understanding of the correlation between the microbial communities and organic acids is limited in the fermentation process of traditional Chinese sour porridge (CSP). In this study, the dynamic of bacterial community and organic acids was investigated and the correlation between bacterial communities and organic acids was revealed during the fermentation process of CSP. The results showed that the richness and diversity of the bacterial communities at initial state (0h) were significantly higher than other period and the concentration of 9 organic acids (oxalic acid, tartaric acid, malic acid, lactic acid, acetic acid, citric acid, and succinic acid) increased with the fermentation process. Pediococcus and Lactobacillus were the dominative genus in the fermentation process of CSP and the fermentation process of CSP can be divided into three stages, with 0 h as the initial stage, 6–18 h as the second group and 24–36 h as the third based on PCA and cluster analysis. Moreover, 20 bacteria genus had significant correlation with (|ρ|>0.7) organic acids based on O2PLS analysis and The Lactobacillus and Acinetobacter were positively correlated with seven (succinic acid, tartaric acid, lactic acid, oxalic acid, acetic acid, malic acid and succinic acid) and four (tartaric acid, acetic acid, lactic acid, and α-ketoglutarate) organic acids respectively. Clostridium, Paenibacillus, Cupriavidus, Shinella, Streptococcus, Flavobacterium, Enterobacteriaceae, Cyanobacteria, Pseudomonas, Ralstonia, Microbacterium, Bradyrhizobiaceae, Escherichia-Shigella, Acidovorax, Leuconostoc, Alphaproteobacteria, Pediococcus, and Mitochondria were negatively correlated with organic acids in the fermentation process of CSP.